If you have (3^4)^3 then you multiply the two exponents to get 3^12. if you have 3^4 x 3^3 then you add the exponents to get 3^7
<em>Greetings from Brasil...</em>
Be that unknown number X
Then we can write the following expression:
X + 4.7 = 8.1
<h2>X = 3.4</h2>
Answer:
Both of these values don't have asymptotes.
Answer:
x = 2
Step-by-step explanation:
<u>Step 1: Convert words into an expression</u>
What is the value of x in the equation 13 x minus 2 (8 + 5 x) = 12 minus 11 x?
13x - 2(8 + 5x) = 12 - 11x
<u>Step 2: Distribute</u>
13x - 2(8 + 5x) = 12 - 11x
13x - 16 - 10x = 12 - 11x
<u>Step 3: Solve for x</u>
13x - 16 - 10x + 11x + 16 = 12 - 11x + 11x + 16
14x / 14 = 28 / 14
x = 2
Answer: x = 2